Pengaruh Pelatihan Pemadam Kebakaran terhadap Peningkatan Pengetahuan terkait Pemadaman Kebakaran pada Mahasiswa Peminatan Keselamatan dan Kesehatan Kerja - Izzatul Alifah Sifai; Lena Aurumia Songraya; Indah Permatasari; Bayu Yoni Setyo Nugroho (Health Science Udinus, 2023)
Firefighter training aims to increase knowledge and skills regarding fire early warning systems so that participants who take part in the training are expected to have the right knowledge and attitude in rescue efforts in the event of a fire. Occupational safety and health students are able to identify and deal with fires. The training is carried out under the guidance of a firefighting instructor. This study aims to examine the effect of fire fighting training on the knowledge of students specializing in Occupational Safety and Health. This research is quantitative in nature and uses a quasi-experimental pretest-posttest design without a control group. The sample in this study were 74 respondents who were selected based on total sampling. Data analysis using the Wilcoxon test showed results (p = 0.000). These results show a difference after receiving firefighting training. The conclusion in this study is that firefighting training has an impact on knowledge related to firefighting among occupational safety and health students.